Gut and Vaginal Microbiomes in PCOS: Implications for Women’s Health - Gu, Yuanyuan; Zhou, Guannan; Zhou, Fangyue; Li, Yao; Wu, Qiongwei; He, Hongyu; Zhang, Yi; Ma, Chengbin; Ding, Jingxin; Hua, Keqin (Frontiers in Endocrinology, 2022)
PCOS is defined as a kind of endocrine and metabolic disorder which affects females at reproductive ages, is becoming much more common, nowadays. Microbiomes are known as microorganisms that inhabit the body to play a vital role in human health. In recent years, several basic and clinical studies have tried to investigate the correlation between the reproductive health/disorder and microbiomes (gut microbiomes and vaginal microbiomes). However, the mechanism is still unclear. In this review, we reviewed the relationship between PCOS and microbiomes, including gut/vaginal microbiomes compositions in PCOS, mechanism of microbiomes and PCOS, and then collectively focused on the recent findings on the influence of microbiomes on the novel insight regarding the therapeutic strategies for PCOS in the future clinical practice.